Prescription patterns and clinical perspectives on intranasal corticosteroids in allergic rhinitis: insights from a nationwide survey of ENT specialists in India - Pandit, Gayatri S.; Khobragade, Kunal; Doshi, Nitinkumar S. (International Journal Of Community Medicine And Public Health, 2025)
Background: Allergic rhinitis (AR) is an atopic disorder that presents with symptoms like nasal congestion, watery nasal discharge, sneezing, postnasal drip, and nasal itching. The worldwide prevalence of AR is about 10% to 25% and in children the prevalence rate is up to 40%. In India, around 20-30% of the population suffers from AR. The objective of this survey was to assess knowledge, attitude, and prescription patterns of intranasal corticosteroids (INCS) in the management of AR among ear-nose-throat (ENT) specialist in India. Methods: A cross-sectional, real-world, in-clinic survey was conducted among 625 ENT specialists across India from August 2024 to October 2024. The respondents were administered a validated 30 questions survey. Results: In the survey, 62.24% of ENT specialists consistently prescribe INCS for AR management, with 84.48% of them prefer fluticasone furoate. Most specialists (69.12%) prescribe INCS for a duration of 1 to 3 months, and 50.88% always use INCS for seasonal AR. Around 55.52% consider age as a key factor while prescribing INCS. For elderly patients 80.96% of the specialist preferred fluticasone furoate. Additionally, 89.12% believe INCS are the most effective AR treatment, and 76.00% routinely educate patients on proper nasal spray techniques. Conclusions: The survey suggests that INCS are the top choice among ENT specialists for treating AR due to their efficacy and safety. Among the INCS, fluticasone furoate was the most preferred molecule. INCS play a key role in enhancing patients’ quality of life and delivering positive clinical outcomes.